2015
DOI: 10.1177/0141076815588320
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraceptives and asthma in women of reproductive age: analysis of data from serial national Scottish Health Surveys

Abstract: Objectives: Sex steroid hormones may explain known gender-related variations in asthma prevalence and clinical manifestation. We investigated the relationship between use of hormonal contraceptives and asthma in women, and assessed evidence of biological interaction between use of hormonal contraceptives and body mass index in this relationship. Design: Population-based analysis using data from serial Exposure: Current use of hormonal contraceptives. Main outcome measures: Self-reported current physiciandiagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 32 publications
(63 reference statements)
0
24
3
2
Order By: Relevance
“…A total of 22,488 records were retrieved, of which 64 articles (reporting 57 studies) met the criteria to be included in the review. E5 , E10 , E11 , E12 , E13 , E14 , E15 , E16 , E17 , E18 , E19 , E20 , E21 , E22 , E23 , E24 , E25 , E26 , E27 , E28 , E29 , E30 , E31 , E32 , E33 , E34 , E35 , E36 , E37 , E38 , E39 , E40 , E41 , E42 , E43 , E44 , E45 , E46 , E47 , E48 , E49 , E50 , E51 , E52 , E53 , E54 , E55 , E56 , E57 , E58 , E59 , E60 , E61 , E62 , E63 , E64 , E65 , E66 , E67 , E68 , E69 , E70 , E71 , E72 In total, 554,293 participants were analyzed across the included studies. Of the 57 studies, 22 were included in at least ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 22,488 records were retrieved, of which 64 articles (reporting 57 studies) met the criteria to be included in the review. E5 , E10 , E11 , E12 , E13 , E14 , E15 , E16 , E17 , E18 , E19 , E20 , E21 , E22 , E23 , E24 , E25 , E26 , E27 , E28 , E29 , E30 , E31 , E32 , E33 , E34 , E35 , E36 , E37 , E38 , E39 , E40 , E41 , E42 , E43 , E44 , E45 , E46 , E47 , E48 , E49 , E50 , E51 , E52 , E53 , E54 , E55 , E56 , E57 , E58 , E59 , E60 , E61 , E62 , E63 , E64 , E65 , E66 , E67 , E68 , E69 , E70 , E71 , E72 In total, 554,293 participants were analyzed across the included studies. Of the 57 studies, 22 were included in at least ...…”
Section: Resultsmentioning
confidence: 99%
“… E4 Data extraction and risk-of-bias assessment were undertaken by N.M. and U.N. for the study authored by B.I.N. and A.S. E5 …”
Section: Methodsmentioning
confidence: 99%
“…The obesity-related risk for asthma was more pronounced in women who did not use oral contraceptives (OR 2.97, 95 % CI 2.80, 3.15) than in those taking oral contraceptives (OR 2.06, 95 % CI 1.89, 2.24). Results from other studies indicated that oral contraceptive use lowered the risk for asthma in girls during puberty [ 33 ] and decreased the risk for asthma and asthma exacerbations in Scottish women [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Так, 30,9 % женщин применяли контрацептивы (95%-ный ДИ -29,3-32,5), при этом использование любой формы контрацепции ассоциировалось со снижением риска диагностирования БА (ОШ -0,68; 95%-ный ДИ -0,47-0,98), а также со снижением риска обострения БА за последние 12 мес. (ОШ -0,45; 95%-ный ДИ -0,47-0,98) [37]. В некоторых исследованиях для выявления ассоциации БА с гормональными механизмами регуляции изучалось влияние эндокринных факторов и оценивалось влияние препаратов эстрогена.…”
Section: влияние эндокринных факторовunclassified